Compact and high repetition rate Kerr-lens mode-locked 532 nm Nd:YVO4 laser. (9th October 2015) - Li, Zuohan; Peng, Jiying; Yuan, Ruixia; Wang, Tongtong; Yao, Jianquan; Zheng, Yi
Abstract: A compact and feasible CW Kerr-lens-induced mode-locked 532 nm Nd:YVO4 laser system was experimentally demonstrated for the first time with theoretical analysis. Kerr-lens mode locking with intracavity second harmonic generation provides a promising method to generate a high-repetition-rate picosecond green laser. With an incident pump power of 6 W, the average output power of mode locking was 258 mW at a high repetition rate of 1.1 GHz.